Elaboration of the Calculation Algorithm for the Load Diagram of a Thermoelectric Generator that Applies the Temperature Dependent Thermoelectric Layer Properties - Golubev R.O.; Stolyarov S.P. (Problems of the Regional Energetics)
The aim of the work is the development of the algorithm for the working parameters calculation of a marine waste heat thermoelectric generator, where the thermoelectric layer properties are considered as temperature dependent. The marine thermoelectric generator must have an exten-sive operational profile that includes a number of modes with a different power demand and different magnitudes of the waste heat parameters. The working mode alteration involves the change in the thermoelectric properties. To achieve the goal a mathematical model was offered for a load diagram calculation. The load diagram represents the generator parameters alteration with respect to the load current change. The most important result was the proposed new order of calculation that differs from the present models with offered variables, an approach to con-structional thermal resistances application and a specific electrical power implementation. Mean temperature and load factor are taken as variables with the load factor being accepted as a rela-tion between the electrical resistances of a load and a generator. Constructional thermal re-sistances were combined into two complex parameters – the thermal resistances of a hot and cold sides. The significance of the obtained results is determined by shaping a versatile approach to the generator`s working parameters calculation. The methodology is independent of the scheme of the calculated generator`s thermal resistances, which could be transformed into the complex parameters. The specific power calculation allows defining the performance per a cross-sectional unit area. The optimal selection of variables reduces the computational time.